Penguatan Karakter Disiplin Siswa Melalui Pembelajaran Pendidikan Agama Islam di SMK NU Kejajar Wonosobo - Abdullah Atana Alqosimi; Sri Haryanto; Salis Irvan Fuadi (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study aims to describe and analyze the efforts to strengthen students' disciplinary character through the learning of Islamic Religious Education at SMK NU Kejajar Wonosobo. To identify the problems in this research, the author uses a descriptive qualitative research methodology with a case study method. The results of this study show that: 1) This study shows that Islamic Religious Education learning at SMK NU Kejajar Wonosobo has a significant contribution in shaping and strengthening students’ disciplinary character. 2) The strategies used by Islamic Religious Education teachers include: integration of disciplinary values into teaching materials, instilling exemplary behavior through the teacher’s attitude, implementation of participatory learning methods, as well as reinforcement through religious advice and habituation of worship such as congregational prayers. 3) The internal inhibiting factor lies in some students who still have a low level of awareness of the importance of discipline, whether in terms of time, assignments, or obedience to school and religious rules. Furthermore, habituation activities such as tadarus or congregational prayers are sometimes not optimally supervised, so students do not perform them earnestly and only as a formality.The supporting factor in this activity is: Islamic Religious Education teachers at SMK NU Kejajar not only deliver theoretical material, but also provide real examples of discipline in attitude and behavior. Teachers arrive on time, are friendly yet firm, and are consistent in guiding students both inside and outside the classroom.